A Study on the Effect of Professionality of Franchise Education Program on the Satisfaction, Work Efficiency and Business Performance - Song, Ji-Hyun; Jo, Gye-Beom (韓國컴퓨터情報學會論文誌, 2019)
In this paper, We analyze the effect of professionality of franchise education program on the satisfaction, work efficiency and business performance, to find how to develop education program which is considered as important in franchise management and to propose ways of sustainable operation of franchise education program. In this study, we carried out survey for 224 users who have competed franchise education programs. We divided the professionality of franchise education program into education instructors, education contents, education environment and education methods through precedent study. For the verification of study hypothesis, we used single regression and multiple regression analysis to verify the relationship between variables. The core study results are as follows. First, professionality of franchise education program is positively related to the satisfaction. Second, professionality of franchise education is positively related to work efficiency. Third, satisfaction affects work efficiency. Fourth, satisfaction and work efficiency have positive effect on business performance. Based on these study results, we found that if education program suitable for the industry and subjects from instructors to education method is developed to improve the professionality of franchise program and continuous communication and improvement is made to increase satisfaction and work efficiency, the franchise education program will create good results. 본 연구는 프랜차이즈 교육프로그램의 전문성이 만족도, 업무효율성, 경영성과에 어떠한 영향를 미치는가를 분석하여, 프랜차이즈 경영에서 중요시되는 교육프로그램을 어떠한 방식으로 개발해야 하는지 그 방법을 찾는데 목적이 있으며, 프랜차이즈 교육프로그램의 지속적인 운영방안을 제안하고자 한다. 본 연구에서는 프랜차이즈 교육프로그램을 이수한 경험이 있는 이용자 224명을 대상으로 설문을 실시하였다. 선행연구를 통해 프랜차이즈 교육프로그램의 전문성을 교육강사, 교육내용, 교육환경, 교육방법으로 구분하였다. 연구가설의 검증을 위하여 단일 회귀분석, 다중회귀 분석을 실시하여 변수간이 관계를 검증하였다. 핵심 연구결과를 정리해보면 첫째, 프랜차이즈 교육프로그램의 전문성이 만족도에 긍정적 관계가 있는 것으로 나타났다. 둘째, 프랜차이즈 교육프로그램의 전문성이 업무효율성에 긍정적 관계가 있는 것으로 나타났다. 셋째, 만족도는 업무효율성에 영향을 미치는 것으로 나타났다. 넷째, 만족도와 업무효율성은 경영성과에 긍정적인 영향을 미치는 것으로 나타났다. 이러한 연구결과로 볼 때 프랜차이즈 교육프로그램의 전문성 향상을 위하여, 교육강사에서 시작하여 교육방법까지 업종과 대상에 맞는 교육 프로그램을 개발하고, 만족도와 업무효율성을 높이기 위하여 지속적인 소통과 개선이 이루어지면, 좋은 성과를 낼 수 있는 프랜차이즈 교육프로그램이 될 것이다.